Month-Wise Prevalence of Subclinical Mastitis in Dairy Cows in Guangdong Province, China - Jin-bo YANG; Neng WEI; Liu-fa WEN (Journal of Integrative Agriculture, 2012)
To evaluate the month-wise prevalence of subclinical mastitis (SM) and its relations with climatic temperature and humidity, and to provide references for control and prevention of mastitis in dairy cows in Guangdong, China, California mastitis test method was used to determine the monthly prevalence of SM (MPSM, %) of lactating Holstein cows from 11 dairy farms in Guangdong Province, China, including about 516 cows per monthly examination. The average MPSM on a cow and a quarter basis were 30 and 13% respectively, and there was a positive linear correlation between monthly mean air temperature (MT, ?C) and MPSM on a cow basis (r=0.763, P=0.004) or a quarter basis (r=0.577, P=0.049), but there were no correlations between MT and MPSM on a cow or a quarter basis (P>0.05). There was a shift in MPSM trend that the highest MPSM (38.4%) was not for the hottest July with MT at 30.8?C, but for the later September at 27.9?C. The farms need to develop new housing conditions to control cowshed temperatures in the hot season to reduce the mastitis prevalences in the posthot months.